PERAN PENGHINDARAN PAJAK DALAM MEMEDIASI PENGARUH CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP PROFITABILITAS PERUSAHAAN - Riny (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This study aims to analyze the role of tax avoidance in mediating the effect of corporate governance and leverage on company profitability. The population in this study was 338 companies. The sampling method used was purposive sampling and obtained 132 companies as objects of research. The research data was obtained from the financial statements of service companies listed on the Indonesia Stock Exchange for the period 2013-2016. The data testing method used is multiple linear analysis and path analysis. The results of the first regression analysis show that partially independent commissioners, audit committees have no significant effect on tax avoidance, while leverage has a significant effect on tax avoidance. The results of the second regression analysis showed that partially, independent commissioners, leverage had no significant effect on profitability, while the audit committee had a significant effect on profitability. The results of the path analysis show that tax avoidance functions as an intervening variable for the independent commissioner.